MUTUAL PHASE-LOCKING OF TWO NANO-SIZE MAGNETIC STRUCTURES CONSIDERING AN INFLUENCE OF SIGNAL DELAY - Prokopenko, O. V. (Radio Electronics, Computer Science, Control, 2011)
Possibility of mutual phase-locking of two interacting nanosize magnetic structures (NMS) is considered taking into account time delay. The dependence of NMS phase-locking bandwidth on the distance between them is shown to have a nonlinear, oscillatory nature. An optimal distance between NMS is determined; the obtained results can be used for creation of phase-locked NMS arrays.